2010
DOI: 10.2174/138161210793563554
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Approach of Primary Bone Tumours by Bisphosphonates

Abstract: Bone tumours can be dissociated in two main categories: i) primary bone tumours (benign or malignant) including mainly osteosarcoma and other sarcomas.ii)and giant cell tumour and bone metastases originate from others cancer (Breast, prostate, kidney cancer, etc). These tumours are able to destroy or/and induce a new calcified matrix. However, the first step of bone tumour development is associated with an induction of bone resorption and the establishment of a vicious cycle between the osteoclasts and the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 85 publications
0
21
0
1
Order By: Relevance
“…High doses of ZOL have been proposed as adjuvant therapy for the treatment of malignant primary bone tumors (osteosarcoma and Ewing sarcoma; 4, 13) that mainly affect children and young adults [25,26]. The principal objectives of high doses zoledronic acid protocol were not only to protect bone from the tumor-induced osteolysis but also to target tumor cells [27], ZOL being a powerful inhibitor of the mevalonate pathway [28]. Our previous studies have evidenced that high doses of ZOL in mouse, similar to the human pediatric treatment, induced a transient arrest of the axial and appendicular skeleton growth of long bones [20].…”
Section: Discussionmentioning
confidence: 99%
“…High doses of ZOL have been proposed as adjuvant therapy for the treatment of malignant primary bone tumors (osteosarcoma and Ewing sarcoma; 4, 13) that mainly affect children and young adults [25,26]. The principal objectives of high doses zoledronic acid protocol were not only to protect bone from the tumor-induced osteolysis but also to target tumor cells [27], ZOL being a powerful inhibitor of the mevalonate pathway [28]. Our previous studies have evidenced that high doses of ZOL in mouse, similar to the human pediatric treatment, induced a transient arrest of the axial and appendicular skeleton growth of long bones [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they observed that the activity of TNF-α was effectively inhibited in the aqueous phase of lung fluids of patients with ARDS. TNF-α has also been suggested to induce the release of IL-6 by endothelial cells and macrophages (42).…”
Section: Discussionmentioning
confidence: 99%
“…We used the nitrogen-containing bisphosphonate, Zol, which has been shown to be a potent inhibitor of osteoclasts and tumor growth in a variety of solid tumors [14, 3235]. Nitrogen-containing bisphosphonates, such as Zol interfere with the mevalonate pathway by inhibiting farnesyl pyrophosphate synthase [36].…”
Section: Discussionmentioning
confidence: 99%